Entre a memória e a autobiografia: narrativas de Cyro dos Anjos e de Darcy Ribeiro - Geraldo da Aparecida Ferreira (2013)
We intend to discuss the formal strategies and the literary construction of the narrative (the narrator, intertextuality, autobiographical pact, the space of the autobiography, among others), and, in addition to that, well articulate these aspects with the social, historical and cultural context. Our corpus is composed by the books O amanuense Belmiro and A menina do sobrado, by Cyro dos Anjos, and Migo and Confissões, by Darcy Ribeiro. We believe that when we address the fruitful issues the role of the intellectual in Brazilian issues of the last century and today, the fragmentary condition of the narrators, the ratio memory / forgetfulness and its importance for the construction of an autobiographical narrative from the perspective of these illustrious writers will be contributing in a quite interesting broader of view, to a wider range of possibilities for reading the works in question.